Preparation method and application of copper-doped ZSM-5 zeolite molecular sieve containing mesoporous structure

The copper-doped mesoporous ZSM-5 zeolite molecular sieve catalyst was synthesized by in-situ doping hydrothermal method, which solved the problems of high cost, difficult to preserve, and difficult to recycle in the prior art, and achieved efficient and environmentally friendly catalytic synthesis of alkenyl silicon compounds, with a yield of up to 99%.

CN117430128BActive Publication Date: 2025-04-25CHANGZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311365760.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-25
Estimated Expiration
2043-10-20

AI Technical Summary

Technical Problem

In the prior art, the catalysts that catalyze α-based silicon compounds have problems such as high cost, difficult to store, and difficult to recycle, and have the disadvantages of long catalytic reaction time, large energy consumption, and heavy metals pollute the environment.

Method used

Copper-doped mesoporous ZSM-5 zeolite molecular sieve catalyst was synthesized by in-situ doping hydrothermal method to catalyze the decarboxylation coupling reaction of cinnamic acid and triphenylsilane to prepare alkenyl silicon compounds. The method includes synthesizing Cu-M-ZSM-5 molecular sieve catalyst under hydrothermal conditions under quaternary ammonium salt templates.

Benefits of technology

The catalyst is achieved with high activity, stability and recyclable use, the catalytic reaction is efficient and environmentally friendly, with a yield of up to 99%, and the catalyst remains highly active after multiple recycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117430128B_ABST
    Figure CN117430128B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a copper-doped ZSM-5 zeolite molecular sieve containing a mesoporous structure and its application in catalyzing the decarboxylation silylation reaction of cinnamic acid and triphenylsilane to synthesize vinyl silicon compounds. The invention adopts an in-situ doping hydrothermal method, uses tetraethyl orthosilicate, aluminum sulfate and copper salt as raw materials, and in the presence of a quaternary ammonium salt template agent, prepares a copper-doped ZSM-5 zeolite molecular sieve containing a mesoporous structure, and has a specific surface area of ​​353 to 422 m 2 / g, silicon-aluminum ratio of 10:1-80:1, crystallinity of 80-100%. The synthesis method of the present invention is easy to operate and has good reproducibility. Compared with the existing homogeneous copper salt catalyst, the copper-doped mesoporous ZSM-5 molecular sieve prepared by the present invention has higher catalytic activity, good reusability and no metal loss in the process of catalyzing the decarboxylation silylation reaction of cinnamic acid and triphenylsilane, and the yield of the alkenyl silicon compound obtained by catalysis is as high as 99%, which has good application prospects in the field of organic catalytic synthesis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic catalytic synthesis, and specifically relates to a preparation method and application of a copper-doped ZSM-5 zeolite molecular sieve containing a mesoporous structure. Background Art

[0002] Vinyl silicon compounds are an important class of chemical raw materials and organic synthesis intermediates. They play an important role in the development of the national economy and are widely used in organic synthesis, metal organic chemistry, medicinal chemistry, and materials science. For example, vinyl silicon compounds can be used to synthesize the industrial flavor dihydrojasmone, can be used to construct the biomacromolecule Senoxydene unsaturated five-membered ring cyclization reaction, and can also be used as organosilicon reagents in palladium-catalyzed Hiyama coupling reactions and oxidation reactions.

[0003] At present, the synthesis of alkenyl silicon compounds is mainly obtained by the hydrosilation reaction of terminal alkynes and silanes or the decarboxylation coupling reaction of α,β-unsaturated acids and silane compounds. Deng Liang et al. used phenylacetylene and triethylsilane as raw materials, nitrogen heterocyclic carbene-coordinated binuclear cobalt carbonyl complex [(IPr)2Co2(CO)6] as catalyst, tetrahydrofuran as solvent, and reacted at 60°C for 5 hours to achieve the selective Markovnikov hydrosilation reaction of terminal alkynes and tertiary silanes to synthesize α-triethylsilyl styrene with a yield of 96%. However, the carbene transition metal complex catalyst used is expensive, difficult to preserve, and difficult to recycle (DYWang, YH Lai, P. Wang, XB Leung, J. Xiao, L. Deng. J. Am. Chem. Soc., 2021, 143, 12847–12856). In 2016, Liu Zhongquan et al. used (E)-3-(4-methoxyphenyl) acrylic acid and triphenylsilane as raw materials, CuCl as catalyst, tert-butyl hydroperoxide as oxidant, tert-butyl alcohol as solvent, reacted at 110°C for 24 hours, and obtained alkenyl silicon compounds by decarboxylation silylation reaction with a yield of 82%. However, the catalyst used was a homogeneous metal salt catalyst, which had problems such as difficulty in catalyst recovery, long decarboxylation coupling reaction time, high energy consumption, and heavy metal pollution of the environment, which did not meet the requirements of sustainable chemistry and green chemistry (LZ Zhang, ZJ Hang, ZQ Liu. Angew. Chem. Int. Ed., 2016, 128, 244-247). Therefore, it is of great significance to develop a low-cost, highly active and recyclable heterogeneous catalyst for efficient catalytic synthesis of alkenyl silicon compounds.

[0004] Mesoporous ZSM-5 zeolite molecular sieve has the advantages of large specific surface area, rich pore structure and ordered mesoporous channels, which are conducive to the adsorption, catalysis and desorption of reactants, making it widely used in various catalytic fields such as petrochemicals, fine chemicals and environmental protection as a kind of green and environmentally friendly heterogeneous catalyst. Cu-doped or loaded mesoporous ZSM-5 zeolite molecular sieve catalyst not only has the advantages of mesoporous ZSM-5 molecular sieve, but also the copper ions introduced into the molecular sieve framework increase the catalytic active sites, which can be used for efficient catalytic conversion of industrial acrylonitrile waste gas and selective catalytic reduction of NO in gas flue gas. Wang Shudong et al. prepared Cu-loaded ZSM-5 molecular sieve by impregnation method to catalyze the combustion of acrylonitrile waste gas. At 320°C, acrylonitrile can be completely converted into pollution-free N2 (Xu Dekang, Wang Sheng, Ding Ya, Zhang Lei, Wang Mingzhe, Wang Shudong. Industrial Catalysis, 2019, 27, 39-44). Zhang Runduo et al. prepared Cu-doped mesoporous ZSM-5 molecular sieve by ion exchange method to catalyze the selective reduction of NO to N2, and can achieve complete conversion of NO at 200-400°C (H.Wang, J.Jia, S.Liu, H.Chen, Y.Wei, Z.Wang, L.Zheng, Z.Wang, R.Zhang.Environ.Sci.Technol.2021,55,5422-5434). However, so far, there is no relevant literature report on the application of copper-containing mesoporous ZSM-5 molecular sieve catalysts in the catalytic decarboxylation coupling reaction of cinnamic acid and triphenylsilane.

[0005] Therefore, it is of great scientific significance and application value to research and develop copper-containing mesoporous ZSM-5 molecular sieves with high activity, good stability and recyclability, and to use them to efficiently catalyze the decarboxylation silylation reaction of cinnamic acid and triphenylsilane to synthesize vinyl silicon compounds. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a copper-doped ZSM-5 zeolite molecular sieve containing a mesoporous structure, characterized in that the structure of the molecular sieve is Cu-nSi-Al-ZSM-5, wherein n represents the molar ratio of Si / Al, n=10-80;

[0009] The ZSM-5 zeolite molecular sieve containing a mesoporous structure has a characteristic X-ray powder diffraction pattern as shown below:

[0010]

[0011]

[0012] The X-ray powder diffraction pattern is based on a relative intensity scale, wherein the strongest line in the X-ray powder diffraction pattern is assigned a value of 100, and the corresponding relative intensities are: w represents weak, i.e. ≤20; m represents medium, i.e. >20 to ≤40; s represents strong, i.e. >40 to ≤60; and vs represents very strong, i.e. >60.

[0013] As a preferred embodiment of the ZSM-5 zeolite molecular sieve of the present invention, the specific surface area of ​​the ZSM-5 zeolite molecular sieve is 353 to 422 m 2 / g, the silicon-aluminum ratio is 10:1 to 80:1, and the crystallinity is 80 to 100%.

[0014] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing ZSM-5 zeolite molecular sieve, characterized in that: comprising:

[0015] Dissolve tetraethyl orthosilicate in deionized water, add concentrated sulfuric acid to adjust the pH to 1.0, then add copper salt, quaternary ammonium salt and aluminum sulfate, stir evenly and adjust the pH of the solution to 9.8 with sodium hydroxide;

[0016] The mixed solution is transferred to a hydrothermal autoclave with a polytetrafluoroethylene liner and crystallized at a constant temperature for a period of time;

[0017] The product was washed with deionized water and anhydrous ethanol, dried, and calcined at 550° C. for 5 hours to obtain a copper-doped mesoporous ZSM-5 molecular sieve catalyst Cu-M-ZSM-5.

[0018] As a preferred embodiment of the preparation method of the present invention, the molar ratio of tetraethyl orthosilicate to aluminum sulfate is 10:1 to 80:1.

[0019] As a preferred embodiment of the preparation method of the present invention, the quaternary ammonium salt is one or more of tetraethylammonium bromide, tetrapropylammonium bromide, and hexadecyltrimethylammonium bromide, and 0.01 to 1.5 g of the quaternary ammonium salt is used for every 1 g of tetraethyl orthosilicate; and the copper salt is one or more of copper nitrate, copper acetate, copper sulfate, and copper chloride, and 0.01 to 0.07 g of the copper salt is used for every 1 g of tetraethyl orthosilicate.

[0020] As a preferred embodiment of the preparation method of the present invention, the constant temperature crystallization is performed for a period of time at a certain temperature, wherein the crystallization temperature is 130-250° C. and the crystallization time is 1-10 days.

[0021] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of a ZSM-5 zeolite molecular sieve, characterized in that the ZSM-5 zeolite molecular sieve is used to catalyze the decarboxylation silylation reaction of cinnamic acid and triphenylsilane to prepare an alkenyl silicon compound, wherein the preparation method is to mix cinnamic acid, triphenylsilane, a ZSM-5 zeolite molecular sieve catalyst Cu-M-ZSM-5, an oxidant and a solvent, and react at 60 to 180° C. for 1 to 24 hours to obtain the alkenyl silicon compound.

[0022] As a preferred embodiment of the application of the present invention, the cinnamic acid is at least one of cinnamic acid and its derivatives, 3-fluorocinnamic acid, 3-chlorocinnamic acid, 3-bromocinnamic acid, 2-methoxycinnamic acid and 2-methylcinnamic acid; the triphenylsilane is at least one of triphenylsilane and its derivatives, triethylsilane and dimethylphenylsilane; the molar ratio of the cinnamic acid to the triphenylsilane is 1:1 to 1:10; and the added amount of the Cu-M-ZSM-5 molecular sieve catalyst is 0.1 to 10% of the molar ratio of the cinnamic acid.

[0023] As a preferred embodiment of the application of the present invention, the oxidant is one of tert-butyl hydroperoxide and di-tert-butyl peroxide, and every 0.1 mmol of cinnamic acid corresponds to 0.1 to 0.7 mmol of the oxidant; the solvent is one or more of tert-butyl alcohol, dichloroethane, acetonitrile, methanol, toluene, and isopropanol, and every 0.1 mmol of cinnamic acid corresponds to 0.25 to 2.5 ml of the solvent.

[0024] As a preferred embodiment of the application of the present invention, the alkenyl silicon compound can be applied to the fields of organic synthesis, organometallic chemistry, medicinal chemistry, and material science.

[0025] Beneficial effects of the present invention:

[0026] (1) The Cu-M-ZSM-5 molecular sieve catalyst synthesized by the in-situ doping hydrothermal method of the present invention has the advantages of easy separation, high activity, good stability, long service life and long storage time. Compared with the ion exchange method and the impregnation method, the Cu-M-ZSM-5 molecular sieve synthesized by the in-situ doping hydrothermal method not only prevents the aggregation of Cu particles and ensures that the active Cu species are stably and evenly dispersed on the mesoporous ZSM-5, but also the synthesized molecular sieve catalyst has good crystallinity and reduces the loss of active metal Cu. The synthesis method in the present invention is easy to operate, has simple equipment requirements and good reproducibility.

[0027] (2) The Cu-M-ZSM-5 molecular sieve catalyst synthesized by the present invention contains alkaline active sites that are beneficial to the adsorption of the reactant cinnamic acid. At the same time, the mesoporous structure contained in the molecular sieve is also beneficial to the adsorption and diffusion of the reactants. The metal Cu active site can catalyze triphenylsilane to form free radical molecules, and then remove a molecule of carbon dioxide, and then undergo a decarboxylation coupling reaction to generate the product E-triphenyl (styryl) silane. This synergistic catalytic effect significantly improves the catalytic activity of the Cu-M-ZSM-5 molecular sieve.

[0028] (3) Experiments show that the mesoporous Cu-M-ZSM-5 molecular sieve prepared by the present invention has higher catalytic decarboxylation coupling reaction performance, and the yield of catalytic decarboxylation silylation of cinnamic acid and triphenylsilane to generate alkenyl silicon compounds is as high as 99%. It can be used in the fields of organic synthesis, organometallic chemistry, medicinal chemistry and material science, and has certain industrial utilization value. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0030] Figure 1 This is a scanning electron microscope image of the Cu-M-ZSM-5 molecular sieve catalyst prepared in Example 1 of the present invention;

[0031] Figure 2 is the X-ray powder diffraction pattern of the Cu-M-ZSM-5 molecular sieve catalyst in Example 1 of the present invention;

[0032] Figure 3 It is a N2 adsorption-desorption curve diagram of the Cu-M-ZSM-5 molecular sieve catalyst in Example 1 of the present invention;

[0033] Figure 4 The product (E)-triphenyl(styryl)silane obtained by the decarboxylation coupling reaction of cinnamic acid and triphenylsilane catalyzed by the Cu-M-ZSM-5 molecular sieve prepared in Example 1 of the present invention is 1 H NMR spectrum;

[0034] Figure 5 The product (E)-triphenyl(styryl)silane obtained by the decarboxylation coupling reaction of cinnamic acid and triphenylsilane catalyzed by the Cu-M-ZSM-5 molecular sieve prepared in Example 1 of the present invention is 13 C NMR spectrum;

[0035] Figure 6This is a diagram showing the catalytic effect of the Cu-M-ZSM-5 molecular sieve catalyst prepared in Example 1 of the present invention being recycled six times. DETAILED DESCRIPTION

[0036] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0037] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0038] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0039] The specifications of the chemical reagents used in the examples of the present invention are shown in Table 1.

[0040] Table 1 Specifications and other information of chemical reagents used in the experiment

[0041]

[0042]

[0043] Example 1

[0044] Weigh 6.8g of tetraethyl orthosilicate and dissolve it in deionized water and mix well. Add concentrated sulfuric acid to adjust the pH to 1.0. Then add 0.2g of copper nitrate trihydrate, 1.8g of tetrapropylammonium bromide and 0.3g of aluminum sulfate. Stir well and adjust the pH of the solution to 9.8 with sodium hydroxide.

[0045] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 180 °C for 5 days;

[0046] The product was washed with deionized water and anhydrous ethanol, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product Cu-M-ZSM-5.

[0047] The product mass was measured to be 1.7 g, the metal content was 1.38 wt%, and the specific surface area was 422 m 2 / g, and the crystallinity is 100%. The information of the equipment models used in the experiment of the present invention is shown in Table 2.

[0048] Table 2. Information on the equipment used in the experiment.

[0049]

[0050] The Cu-M-ZSM-5 molecular sieve material prepared in Example 1 was characterized.

[0051] Thermo Scientific Apreo 2C field emission scanning electron microscope (SEM) was used to analyze the morphology of Cu-M-ZSM-5. Figure 1 As shown in the figure, the scale sizes are 10μm, 1μm, and 200nm respectively. The results show that Cu-M-ZSM-5 is a spherical particle of about 10μm, and its surface is a prismatic structure. In addition, it can be seen from the figure that the crystal phase of Cu-M-ZSM-5 is relatively pure, without other impure amorphous phases, and the morphology and structure are relatively regular.

[0052] The crystal structure and phase of Cu-M-ZSM-5 molecular sieve material were analyzed using a Bruker D / max 2500PC powder X-ray diffractometer (PXRD, Cu Kα radiation, λ=0.15406nm, scanning range 2θ 5°~50°). The test results are shown in Figure 2 As shown in Table 3, the results show that 7.8°, 8.8°, 23.1°, 26.6° and 29.2° are characteristic diffraction peaks of ZSM-5 molecular sieve, showing MFI topological structure. In addition, 30°, 36° and 46° are characteristic diffraction peaks of Cu species, and the material has reliable phase purity. From the peak intensity point of view, the peak intensity of Cu-M-ZSM-5 is strong and the peak shape is very sharp, indicating that the crystallinity of Cu-M-ZSM-5 molecular sieve material is good, which provides a guarantee for its use as a catalyst for the decarboxylation coupling reaction of cinnamic acid.

[0053] Table 3

[0054]

[0055] The specific surface area, N2 adsorption-desorption curve and pore size distribution of Cu-M-ZSM-5 molecular sieve material were determined by Micrometrics ASAP2460 specific surface area and porosity analyzer. The specific surface area was determined by BET method, and the pore size distribution was determined by BJH method. Before the determination, the sample was dried at 120℃ for 2 hours and then placed in a vacuum environment at 150℃ for 12 hours. The results are as follows Figure 3 As shown in the figure, it can be seen that there is a hysteresis loop in the N2 adsorption-desorption curve, which is due to the capillary condensation of N2 in the pores of the molecular sieve, further indicating that Cu-M-ZSM-5 is a mesoporous molecular sieve material. From the pore size distribution curve, it can be seen that the pore size distribution of Cu-M-ZSM-5 is 2.5nm and the pore size distribution is uniform.

[0056] Example 2

[0057] Weigh 6.8g of tetraethyl orthosilicate and dissolve it in deionized water and mix well. Add concentrated sulfuric acid to adjust the pH to 1.0. Then add 0.1g of copper nitrate trihydrate, 1.8g of tetrapropylammonium bromide and 1.2g of aluminum sulfate. Stir well and adjust the pH of the solution to 9.8 with sodium hydroxide.

[0058] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 180 °C for 5 days;

[0059] The product was washed with deionized water and anhydrous ethanol, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product Cu-M-ZSM-5.

[0060] The product mass was measured to be 0.4 g, the metal content was 0.3 wt%, and the specific surface area was 320 m 2 / g, and the crystallinity is 80%.

[0061] Example 3

[0062] Weigh 6.8g of tetraethyl orthosilicate and dissolve it in deionized water and mix well. Add concentrated sulfuric acid to adjust the pH to 1.0. Then add 0.2g of copper nitrate trihydrate, 1.8g of tetraethylammonium bromide and 0.15g of aluminum sulfate. Stir well and adjust the pH of the solution to 9.8 with sodium hydroxide.

[0063] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 180 °C for 5 days;

[0064] The product was washed with deionized water and anhydrous ethanol, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product Cu-M-ZSM-5.

[0065] The product mass was measured to be 1 g, the metal content was 1.1 wt%, and the specific surface area was 400 m 2 / g, and the crystallinity is 93%.

[0066] Example 4

[0067] Weigh 6.8g of tetraethyl orthosilicate and dissolve it in deionized water and mix well. Add concentrated sulfuric acid to adjust the pH to 1.0. Then add 0.17g of copper acetate, 3.6g of hexadecyltrimethylammonium bromide and 0.3g of aluminum sulfate. Stir well and adjust the pH of the solution to 9.8 with sodium hydroxide.

[0068] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 180 °C for 5 days;

[0069] The product was washed with deionized water and anhydrous ethanol, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product Cu-M-ZSM-5.

[0070] The product mass was measured to be 1.5 g, the metal content was 1.12 wt%, and the specific surface area was 390 m 2 / g, and the crystallinity is 95%.

[0071] Example 5

[0072] Weigh 6.8g of tetraethyl orthosilicate and dissolve it in deionized water and mix well. Add concentrated sulfuric acid to adjust the pH to 1.0. Then add 0.13g of copper sulfate, 1.8g of tetrapropylammonium bromide and 0.3g of aluminum sulfate. Stir well and adjust the pH of the solution to 9.8 with sodium hydroxide.

[0073] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 180 °C for 5 days;

[0074] The product was washed with deionized water and anhydrous ethanol, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product Cu-M-ZSM-5.

[0075] The product mass was measured to be 1.2 g, the metal content was 0.82 wt%, and the specific surface area was 382 m 2 / g, and the crystallinity is 89%.

[0076] Example 6

[0077] Weigh 6.8g of tetraethyl orthosilicate and dissolve it in deionized water and mix well. Add concentrated sulfuric acid to adjust the pH to 1.0. Then add 0.11g of copper chloride, 1.8g of tetrapropylammonium bromide and 0.3g of aluminum sulfate. Stir well and adjust the pH of the solution to 9.8 with sodium hydroxide.

[0078] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 180 °C for 5 days;

[0079] The product was washed with deionized water and anhydrous ethanol, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product Cu-M-ZSM-5.

[0080] The product mass was measured to be 1.5 g, the metal content was 1.25 wt%, and the specific surface area was 425 m 2 / g, and the crystallinity is 99%.

[0081] Example 7

[0082] Weigh 6.8g of tetraethyl orthosilicate and dissolve it in deionized water and mix well. Add concentrated sulfuric acid to adjust the pH to 1.0. Then add 0.2g of copper nitrate trihydrate, 0.1g of tetrapropylammonium bromide and 0.3g of aluminum sulfate. Stir well and adjust the pH of the solution to 9.8 with sodium hydroxide.

[0083] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 180 °C for 5 days;

[0084] The product was washed with deionized water and anhydrous ethanol, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product Cu-M-ZSM-5.

[0085] The product mass was measured to be 0.5 g, the metal content was 0.67 wt%, and the specific surface area was 357 m 2 / g, and the crystallinity is 81%.

[0086] Example 8

[0087] Weigh 6.8g of tetraethyl orthosilicate and dissolve it in deionized water and mix well. Add concentrated sulfuric acid to adjust the pH to 1.0. Then add 0.2g of copper nitrate trihydrate, 10g of tetraethylammonium bromide and 0.3g of aluminum sulfate. Stir well and adjust the pH of the solution to 9.8 with sodium hydroxide.

[0088] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 180 °C for 5 days;

[0089] The product was washed with deionized water and anhydrous ethanol, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product Cu-M-ZSM-5.

[0090] The product mass was measured to be 1.3 g, the metal content was 1.25 wt%, and the specific surface area was 388 m 2 / g, and the crystallinity is 95%.

[0091] Example 9

[0092] Weigh 6.8g of tetraethyl orthosilicate and dissolve it in deionized water and mix well. Add concentrated sulfuric acid to adjust the pH to 1.0. Then add 0.2g of copper nitrate trihydrate, 1.8g of tetrapropylammonium bromide and 0.3g of aluminum sulfate. Stir well and adjust the pH of the solution to 9.8 with sodium hydroxide.

[0093] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 130 °C for 10 days;

[0094] The product was washed with deionized water and anhydrous ethanol, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product Cu-M-ZSM-5.

[0095] The product mass was measured to be 0.3 g, the metal content was 0.88 wt%, and the specific surface area was 360 m 2 / g, and the crystallinity is 85%.

[0096] Example 10

[0097] Weigh 6.8g of tetraethyl orthosilicate and dissolve it in deionized water and mix well. Add concentrated sulfuric acid to adjust the pH to 1.0. Then add 0.2g of copper nitrate trihydrate, 1.8g of tetrapropylammonium bromide and 0.3g of aluminum sulfate. Stir well and adjust the pH of the solution to 9.8 with sodium hydroxide.

[0098] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 250 °C for 1 day;

[0099] The product was washed with deionized water and anhydrous ethanol, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product Cu-M-ZSM-5.

[0100] The product mass was measured to be 1.3 g, the metal content was 1.05 wt%, and the specific surface area was 413 m 2 / g, and the crystallinity is 92%.

[0101] Embodiment 11

[0102] Weigh 6.8g of tetraethyl orthosilicate and dissolve it in deionized water and mix well. Add concentrated sulfuric acid to adjust the pH to 1.0. Then add 0.2g of copper nitrate trihydrate, 1.8g of tetrapropylammonium bromide and 0.3g of aluminum sulfate. Stir well and adjust the pH of the solution to 9.8 with sodium hydroxide.

[0103] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 200 °C for 7 days;

[0104] The product was washed with deionized water and anhydrous ethanol, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product Cu-M-ZSM-5.

[0105] The product mass was measured to be 1.5 g, the metal content was 1.25 wt%, and the specific surface area was 420 m 2 / g, and the crystallinity is 99%.

[0106] Comparative Example 1

[0107] The ion exchange method is used to synthesize the Cu-M-ZSM-5 molecular sieve catalyst, comprising the following steps:

[0108] (1) Synthesize M-ZSM-5 molecular sieve by hydrothermal method:

[0109] Weigh 6.8g of tetraethyl orthosilicate and dissolve it in deionized water and mix it evenly. Add concentrated sulfuric acid to adjust the pH to 1.0, then add 1.8g of tetrapropylammonium bromide and 0.3g of aluminum sulfate, stir evenly, and adjust the pH of the solution to 9.8 with sodium hydroxide; transfer the mixed solution to a 50ml polytetrafluoroethylene high-pressure hydrothermal autoclave and crystallize it at a constant temperature of 180°C for 5 days; wash it with deionized water and anhydrous ethanol, dry it, transfer it to a muffle furnace and calcine it at 550°C for 5 hours to obtain the product M-ZSM-5 molecular sieve.

[0110] (2) Preparation of Cu-M-ZSM-5 molecular sieve by ion exchange method:

[0111] Weigh 0.2 g of copper nitrate trihydrate, add 10 ml of deionized water to dissolve it, stir evenly and add the M-ZSM-5 molecular sieve prepared above, stir, perform ion exchange at room temperature, dry at 100°C overnight, press into tablets and sieve to obtain Cu-M-ZSM-5 molecular sieve.

[0112] The product mass was measured to be 1.3 g, the metal content was 0.98 wt%, and the specific surface area was 403 m 2 / g, and the crystallinity is 68%.

[0113] Comparative Example 2

[0114] The preparation of Cu-M-ZSM-5 by an equal volume impregnation method comprises the following steps:

[0115] First, the water absorption rate of the molecular sieve carrier is measured, and the catalyst is impregnated in equal volumes according to the water absorption rate. Weigh 0.2g of copper nitrate trihydrate and dissolve it in deionized water. Add 1g of M-ZSM-5 molecular sieve carrier (silicon-aluminum ratio 25, crystallinity 100%) and stir it thoroughly, and mix it evenly by ultrasound. After aging at room temperature for 5 hours, dry it at 80℃, and calcine it at 550℃ in a muffle furnace for 5 hours to obtain Cu-M-ZSM-5 molecular sieve.

[0116] The product mass was measured to be 1.1 g, the metal content was 1.15 wt%, and the specific surface area was 388 m 2 / g, and the crystallinity is 79%.

[0117] It can be seen from Examples 1 to 11 and Comparative Examples 1 and 2 that the in-situ doping synthesis method has the advantages of more convenient operation, high catalyst yield, high crystallinity, etc. compared with the ion exchange method and the impregnation method. In addition, the interaction between the Cu species in the Cu-M-ZSM-5 catalyst synthesized by in-situ doping hydrothermal synthesis and the M-ZSM-5 molecular sieve is stronger, so that it has higher catalytic activity.

[0118] The following examples screen the condition parameters of the catalytic reaction.

[0119] Example 12

[0120] The performance of the Cu-M-ZSM-5 molecular sieve material in Example 1 in catalyzing the decarboxylation coupling reaction of cinnamic acid was studied.

[0121] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0122] After the reaction is completed, the catalyst is separated by centrifugation, the reaction solution is detected and analyzed by SHIMADZU high performance liquid chromatography, and the product is separated by column chromatography.

[0123] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 99.8%.

[0124] Product 1 H NMR spectrum Figure 4 As shown, 13 C NMR spectrum Figure 5 The NMR analysis of the product is as follows: 1 HNMR (500MHz, DMSO) δ7.61–7.32(m,20H),7.18(d,J=19.1Hz,1H),6.92(d,J=19.1Hz,1H). 13 C NMR (125MHz, DMSO) δ148.8,137.7,135.9,134.4,130.2,129.2,127.2,123.1.

[0125] Test conditions:

[0126] SHIMADZU LC-VP high performance liquid chromatograph was used, and the mobile phase was acetonitrile and water gradient elution (V 乙腈 :V 水 =60:40), UV detector, detection wavelength of 291 nm, flow rate of 1.0 mL / min, injection volume of 20 μL.

[0127] The AVANCE III 500M NMR instrument from Bruker, Germany, was used, with an operating frequency of 500 MHz ( 1H); supershielded magnet, magnetic field strength 9.4T; equipped with a positive broadband liquid probe. Chemical shifts of protons are reported in ppm and are referenced to the deuterated residue in the NMR solvent (DMSO-d6, δ2.50). Chemical shifts of carbon are reported in ppm and are referenced to the carbon resonance of the reference solvent (DMSO-d6, δ39.52). Data represent coupling constants in Hertz (Hz), integrated.

[0128] Example 13

[0129] 0.4 mmol cinnamic acid, 0.4 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0130] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 75.8%.

[0131] Embodiment 14

[0132] 0.4 mmol cinnamic acid, 4.0 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0133] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 97.9%.

[0134] Embodiment 15

[0135] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 0.1 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0136] The structure of the product was confirmed by NMR and HPLC to be (E)-triphenyl(phenylvinyl)silane, and the yield was only 5.7%, indicating that too low a dosage of the Cu-M-ZSM-5 catalyst would greatly reduce the reaction efficiency.

[0137] Example 16

[0138] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 10 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0139] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 98.3%.

[0140] Embodiment 17

[0141] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 0.4 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0142] The structure of the product was confirmed by NMR and HPLC to be (E)-triphenyl(phenylvinyl)silane with a yield of 37.7%, indicating that reducing the amount of the oxidant tert-butyl hydroperoxide used would lead to a decrease in the efficiency of the catalytic reaction, and further indicating that tert-butyl hydroperoxide is crucial to the reaction.

[0143] Embodiment 18

[0144] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 2.8 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added into a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0145] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 96.2%.

[0146] Embodiment 19

[0147] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol di-tert-butyl peroxide and 6 ml tert-butanol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0148] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 65.6%, indicating that when di-tert-butyl peroxide was used as an oxidant in the reaction, the catalytic performance would be reduced.

[0149] Embodiment 20

[0150] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 1 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0151] The structure of the product was confirmed by NMR and HPLC to be (E)-triphenyl(phenylvinyl)silane, with a yield of 45.1%, indicating that reducing the amount of solvent tert-butanol used would reduce the yield of the reaction, further indicating that tert-butanol as a solvent is crucial to the reaction.

[0152] Embodiment 21

[0153] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 3 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0154] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 57.7%.

[0155] Embodiment 22

[0156] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 10 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0157] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 95.8%.

[0158] Embodiment 23

[0159] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml dichloroethane were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0160] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 57.3%, indicating that dichloroethane was not the best choice as solvent for the reaction.

[0161] Embodiment 24

[0162] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml acetonitrile were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0163] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 54.9%, indicating that acetonitrile was not the best choice as solvent for the reaction.

[0164] Embodiment 25

[0165] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml toluene were added into a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0166] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 45.5%, indicating that toluene was not the best choice as solvent for the reaction.

[0167] Embodiment 26

[0168] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml isopropanol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0169] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 30.2%, indicating that isopropanol was not the best choice as solvent for the reaction.

[0170] Embodiment 27

[0171] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added into a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 60° C. for 24 hours.

[0172] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 10.3%, indicating that the reaction temperature and reaction time are crucial to the reaction.

[0173] Embodiment 28

[0174] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 150° C. for 1 hour.

[0175] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 95.2%.

[0176] Embodiment 29

[0177] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 180° C. for 6 hours.

[0178] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 83.5%.

[0179] Embodiment 30

[0180] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 130° C. for 3 hours.

[0181] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 99.1%.

[0182] Embodiment 31

[0183] 0.4 mmol 3-fluorocinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0184] The structure of the product was confirmed to be (E)-(3-fluorophenylvinyl)triphenylsilane by NMR and HPLC, and the yield was 75.6%.

[0185] The NMR analysis of the product is: 1 H NMR (500MHz, DMSO) δ7.62 (dd, J=8.7, 5.6Hz, 2H), 7.51 (dd, J=7.8, 1.4Hz, 6H), 7.43 (ddd, J=1 5.5,7.7,3.6Hz,9H),7.17(t,J=8.8Hz,2H),7.11(d,J=19.1Hz,1H),6.90(d,J=19.1Hz,1H). 13 C NMR (125MHz, DMSO) δ147.5,135.9,134.4,130.2,129.3,128.5,123.0,116.0,115.8.

[0186] Embodiment 32

[0187] 0.4 mmol 3-chlorocinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0188] The structure of the product was confirmed by NMR and HPLC to be (E)-(3-chlorophenylvinyl)triphenylsilane, with a yield of 83.2%.

[0189] The NMR analysis of the product is: 1 H NMR (500MHz, DMSO) δ7.54–7.40(m,17H),7.37–7.34(m,2H),7.30(d,J=19.1Hz,1H),6.90(d,J=19.1Hz,1H). 13 CNMR(125MHz,DMSO)δ147.1,140.0,136.0,134.2,130.9,130.2,128.8,128.6,126.7,126.1,125.6.

[0190] Embodiment 33

[0191] 0.4 mmol 3-bromocinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0192] The structure of the product was confirmed by NMR and HPLC to be (E)-(3-bromostyryl)triphenylsilane with a yield of 71.2%.

[0193] The NMR analysis of the product is: 1 H NMR (500MHz, DMSO) δ7.54–7.41(m,19H),7.23(dd,J=57.0,13.2Hz,1H),6.91(dd,J=19.1,14.5Hz,1H). 13 C NMR (125MHz, DMSO) δ136.0,135.3,134.5,134.2,131.7,131.2,130.3,128.6,128.3,127.2,126.5,125.6.

[0194] Embodiment 34

[0195] 0.4 mmol 2-methoxycinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0196] The structure of the product was confirmed to be (E)-(2-methoxyphenylvinyl)triphenylsilane by NMR and HPLC, and the yield was 80.7%.

[0197] The NMR analysis of the product is: 1 H NMR (500MHz, DMSO) δ7.54–7.37(m,17H),6.99–6.84(m,4H),3.74(s,3H). 13 C NMR (125MHz, DMSO) δ160.2,148.5,135.9,134.7,130.7,130.1,128.7,128.5,119.7,114.4,55.6.

[0198] Embodiment 35

[0199] 0.4 mmol 2-methylcinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0200] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-methylphenylvinyl)triphenylsilane, with a yield of 70.9%.

[0201] The NMR analysis of the product is: 1 H NMR (500MHz, DMSO) δ7.73 (dd, J=13.2, 6.1Hz, 1H), 7.55 (dd, J=7.8, 1.5Hz, 6H ),7.47–7.38(m,9H),7.26–7.11(m,4H),7.03(d,J=19.0Hz,1H),2.13(s,3H). 13 C NMR (125MHz, DMSO) δ136.8,135.9,135.6,134.5,130.8,130.2,128.9,128.5,126.7,125.8,124.5,19.3.

[0202] Embodiment 36

[0203] 0.4 mmol cinnamic acid, 2.8 mmol triethylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0204] The structure of the product was confirmed to be (E)-triethylphenylsilane by NMR and HPLC, and the yield was 86.5%.

[0205] The NMR analysis of the product is: 1 H NMR (500MHz, DMSO) δ7.50 (d, J = 7.4Hz, 2H), 7.35 (t, J = 7.5Hz, 2H), 7.28 (t, J = 7.3Hz, 1H), 6. 93(d,J=19.4Hz,1H),6.47(d,J=19.4Hz,1H),0.96(t,J=7.9Hz,9H),0.64(q,J=7.9Hz,6H). 13 C NMR (125MHz, DMSO) δ145.3,138.2,129.0,128.6,126.7,125.5,7.7,3.5.

[0206] Embodiment 37

[0207] 0.4 mmol cinnamic acid, 2.8 mmol dimethylphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0208] The structure of the product was confirmed by NMR and HPLC to be (E)-dimethyl(phenylvinyl)(phenyl)silane with a yield of 81.3%.

[0209] The NMR analysis of the product is: 1 H NMR (500MHz, DMSO) δ7.57(dd,J=6.5,3.1Hz,2H),7.52(d,J=7.3Hz,2H),7.37(ddd,J=15.2,9.3, 4.9Hz, 5H), 7.29 (t, J = 7.3Hz, 1H), 6.98 (d, J = 19.2Hz, 1H), 6.67 (d, J = 19.2Hz, 1H), 0.42 (s, 6H). 13 C NMR (125MHz, DMSO) δ144.9,138.1,137.5,133.6,129.0,128.6,128.3,127.8,126.8,126.4.

[0210] Embodiment 38

[0211] Recycling of Cu-M-ZSM-5

[0212] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared in Example 1), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added to a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0213] After the reaction, the catalyst was centrifuged, washed several times with deionized water and anhydrous ethanol, and then placed in a drying oven at 100°C for 12 hours. The dried catalyst was recycled six times under the same catalytic conditions. The catalytic effect was as follows: Figure 6 As shown, the results show that the catalytic activity remains unchanged after six cycles.

[0214] Comparative Example 3

[0215] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu nanoparticles, 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added into a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110 °C for 4 h.

[0216] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 5.2%.

[0217] Comparative Example 4

[0218] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% copper nitrate trihydrate, 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added into a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110°C for 4 hours.

[0219] The product (E)-triphenyl(styryl)silane was not detected and the yield was 0%.

[0220] Comparative Example 5

[0221] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% ZSM-5 molecular sieve, 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added into a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0222] The product (E)-triphenyl(styryl)silane was not detected and the yield was 0%.

[0223] Comparative Example 6

[0224] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared by ion exchange method), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added into a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110° C. for 4 hours.

[0225] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 52.2%.

[0226] Comparative Example 7

[0227] 0.4 mmol cinnamic acid, 2.8 mmol triphenylsilane, 3.0 mol% Cu-M-ZSM-5 (prepared by impregnation method), 1.2 mmol tert-butyl hydroperoxide and 6 ml tert-butyl alcohol were added into a 10 ml sealed Schlenk tube with a magnetic stirring bar and reacted at 110°C for 4 hours.

[0228] The structure of the product was confirmed to be (E)-triphenyl(phenylvinyl)silane by NMR and HPLC, and the yield was 78.6%.

[0229] The invention discloses a method for synthesizing a mesoporous Cu-M-ZSM-5 molecular sieve catalyst by in-situ doping hydrothermal reaction of metallic copper and its application in catalyzing the decarboxylation coupling reaction of cinnamic acid to generate alkenyl silicide, and relates to the field of heterogeneous catalysts for constructing alkenyl silicon compounds by decarboxylation coupling reaction. The in-situ doping hydrothermal preparation method is as follows: using tetraethyl orthosilicate, aluminum sulfate and copper salt as raw materials, in the presence of a quaternary ammonium salt template, constant temperature crystallization at 180°C for 5 days to obtain a Cu-M-ZSM-5 molecular sieve catalyst with a specific surface area of ​​353 to 422 m 2 / g, silicon-aluminum ratio of 10:1-80:1, crystallinity of 80-100%. The prepared catalyst has the advantages of economy, high efficiency, green environmental protection, etc., and can improve the disadvantages of homogeneous catalysts that are difficult to recover and recycle. The preparation method of the invention is easy to operate and has good reproducibility.

[0230] The mesoporous Cu-M-ZSM-5 molecular sieve prepared by the invention is used for catalyzing the decarboxylation coupling reaction of cinnamic acid and triphenylsilane, and the yield of the prepared (E)-triphenyl(styryl)silane can be as high as 99%. After the catalyst is recycled for many times, it still maintains a high catalytic activity and has no metal loss. Therefore, the catalyst can be applied in the fields of modern organic catalytic synthesis of organic alkenyl silicon compounds, and has certain industrial application prospects.

[0231] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. An application of a copper-doped ZSM-5 zeolite molecular sieve containing a mesoporous structure, characterized in that: The ZSM-5 zeolite molecular sieve is used to catalyze the decarboxylation silylation reaction of cinnamic acid and triphenylsilane to prepare an alkenyl silicon compound, wherein the preparation method comprises mixing cinnamic acid, triphenylsilane, a ZSM-5 zeolite molecular sieve catalyst Cu-M-ZSM-5, an oxidant and a solvent, and reacting at 60 to 180° C. for 1 to 24 hours to obtain an alkenyl silicon compound; The cinnamic acid is cinnamic acid and its derivatives, and the cinnamic acid derivatives include at least one of 3-fluorocinnamic acid, 3-chlorocinnamic acid, 3-bromocinnamic acid, 2-methoxycinnamic acid, and 2-methylcinnamic acid; the triphenylsilane is at least one of triphenylsilane and its derivatives, triethylsilane, and dimethylphenylsilane; the molar ratio of the cinnamic acid to the triphenylsilane is 1:1 to 1:10; the added amount of the Cu-M-ZSM-5 molecular sieve catalyst is 0.1 to 10% of the molar amount of the cinnamic acid; The oxidant is one of tert-butyl hydroperoxide and di-tert-butyl peroxide, and 0.1 to 0.7 millimoles of the oxidant are corresponding to every 0.1 millimoles of cinnamic acid; the solvent is one or more of tert-butyl alcohol, dichloroethane, acetonitrile, methanol, toluene, and isopropanol, and 0.25 to 2.5 milliliters of the solvent are corresponding to every 0.1 millimoles of cinnamic acid; The alkenyl silicon compound is used in the field of organic synthesis or material science; The structure of the molecular sieve is Cu-nSi-Al-ZSM-5, wherein n represents the molar ratio of Si / Al, and n=10 to 80; The ZSM-5 zeolite molecular sieve containing a mesoporous structure has a characteristic X-ray powder diffraction pattern as shown below: The X-ray powder diffraction pattern is based on a relative intensity scale, wherein the strongest line in the X-ray powder diffraction pattern is assigned a value of 100, and the corresponding relative intensities are: w represents weak, i.e. ≤20; m represents medium, i.e. >20 to ≤40; s represents strong, i.e. >40 to ≤60; and vs represents very strong, i.e. >60.

2. The use according to claim 1, characterized in that: The specific surface area of ​​the ZSM-5 zeolite molecular sieve is 353 to 422 m 2 / g, the silicon-aluminum ratio is 10:1 to 80:1, and the crystallinity is 80 to 100%.

3. The use according to claim 1 or 2, characterized in that: include, Dissolve tetraethyl orthosilicate in deionized water, add concentrated sulfuric acid to adjust the pH to 1.0, then add copper salt, quaternary ammonium salt and aluminum sulfate, stir evenly and adjust the pH of the solution to 9.8 with sodium hydroxide; The mixed solution is transferred to a hydrothermal autoclave with a polytetrafluoroethylene liner and crystallized at a constant temperature for a period of time; The product was washed with deionized water and anhydrous ethanol, dried, and calcined at 550° C. for 5 hours to obtain a copper-doped mesoporous ZSM-5 molecular sieve catalyst Cu-M-ZSM-5.

4. The use according to claim 3, characterized in that: The molar ratio of tetraethyl orthosilicate to aluminum sulfate is 10:1 to 80:

1.

5. The use according to claim 3, characterized in that: The quaternary ammonium salt is one or more of tetraethylammonium bromide, tetrapropylammonium bromide, and hexadecyltrimethylammonium bromide, and 0.01 to 1.5 g of the quaternary ammonium salt is corresponding to 1 g of tetraethyl orthosilicate; the copper salt is one or more of copper nitrate, copper acetate, copper sulfate, and copper chloride, and 0.01 to 0.07 g of the copper salt is corresponding to 1 g of tetraethyl orthosilicate.

6. The use according to claim 3, characterized in that: The constant temperature crystallization is performed for a period of time at a certain temperature, wherein the crystallization temperature is 130-250° C. and the crystallization time is 1-10 days.

Citation Information

Patent Citations

  • Preparation method of Cu-ZSM-5 denitration catalyst by double-template one-step hydrothermal synthesis

    CN106732757A